E-learning through Twitter does effect learning process of students in UiTM Rembau / Nor Intan Nasehar Hamzah - Hamzah, Nor Intan Nasehar (2023)
Twitter is a popular microblogging social networking site, allows individuals to communicate by sending short messages of up to 140 characters. Although it enables people to be in constant contact, its value in educational context is less clear. Twitter shows promise in improving interactions among learners and teachers, causality between Twitter use and learning performance remains to be conclusively established. Currently, the most beneficial use of Twitter is probably that of a "push" technology such as the instructor sending important course information, homework assignments and test deadlines to students, as well as that of a platform for peer interaction. Many challenges still exist in using Twitter for teaching and learning. This research was proposed to know e-learning through Twitter does effect learning process of students in UITM Rembau.